Professionalism and teacher education: social representations of teachers - Dias da Silva, Rejane; Alves Dias, Adelaide; de Almeida Pimenta, Sonia (Revista Diálogo Educacional, 2014)
This study examines the social representation of teacher training of teachers in public schools in Pernambuco State. We assume that the social representations can contribute to trigger educational practices and provide access to their knowledge. Questionnaires were used with 80 teachers from 20 schools in primary and secondary education. We identify the semantic field of social representations of teachers and the elements that constitute the core. The results revealed that the representations about the formation circulate around the educational, academic and professional categories. The professional category was insignificant in the field of representations of the subjects investigated. The core of these representations is organized around the academic dimension. The representations of the training are based on academic category, which indicates the strong influence of initial training in undergraduate programs, although there was substantiated evidence of changes in emphasis in the teaching category found in the representations of teachers.